TINJAUAN YURIDIS TERHADAP HAMBATAN PENEGAKAN HUKUM PERSAINGAN USAHA OLEH KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) - Puspita Dewi, Candra; Sudantra, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
In the writing of scientific papers entitled “Judicial Review Of The Barriers To Competition Law Enforcement (KPPU)”. Writing method used in this paper is the normative legal research. Issues raised in this paper is how the attitude to be taken by the commision if the businesses are not present at the time of the call and how to execute the decisions of the commision if the agency is not willing to payment of compensation and fines. Based on research by the result that the Commission can not force the parties concerned to be present, but the Commission may impose verstek if the reported decision has properly called, but did not attend. During the absence of clear regulations that govern the payment of compensation and fines the Commission can not make an effort force payment of compensation and fines.
Keywords: Judicial Review, Barriers, Execute the decisions, Compensation